(untitled) (CIPEEX, 2025)
MarIA was conceived to understand the primary needs of a physician within a medical office. However, according to field research, the end user reported a need to be closer to their patients, fostering a more humanized doctor-patient relationship. With this in mind, a broader project was envisioned to cater to both the physician and the patient. In this scenario, MarIA becomes an assistive tool for the physician. By integrating artificial intelligence into the system, the primary end-user can perform necessary tasks during a consultation using a few commands, without having to divert their attention from the patient to focus on the computer screen. The goal is to increase doctor-patient interaction, make consultations more fluid, and assist the physician in processes that need to be performed via computer. But the journey doesn’t end there. It was discovered that patients often lose the documents they receive from the doctor during a consultation, such as prescriptions and exam results, necessitating a return to the office to obtain a new copy. Considering this, MarIA will receive an extension in the form of a patient app, fully integrated with the clinic’s system. Within this app, each patient will have a personal profile and can receive and perform actions without always being physically present at the clinic. Any document generated during a consultation will also be generated in the app, ensuring that the patient always has access to these documents with the doctor’s electronic signature and stamp, without having to worry about losing the physical copy. The entire project structure will be developed using an incremental method, Scrum, to ensure that all aspects are addressed cleanly and efficiently, without compromising critical parts of the project’s main structure and allowing for the collection of valuable feedback from our end users.